Trayectorias Socioeconómicas Compartidas (SSP): nuevas maneras de comprender el cambio climático y social - Escoto Castillo, Ana; Sánchez Peña, Landy; Gachuz Delgado, Sheila (El Colegio de México A.C., 2017)
Although the scientific community has recently confirmed the role of human activity in greenhouse gas emissions, there are still major challenges to consider future social transformations and their effects on climate and societies. In this paper, we discuss the use of climate change scenarios as a heuristic tool to examine the interactions between terrestrial and social systems. Particularly, we discuss the usefulness of Shared Socioeconomic Trajectories (SSP) to model alternative development futures, which imply different climate change mitigation and adaptation. We consider on their background, applications and potential uses for Mexico.